The implementation of local wisdom-based learning and HOTS-based assessment: Teacher survey in Banjarmasin - A. Abidinsyah; Siti Ramdiah; Muhammad Royani (University of Muhammadiyah Malang, 2019)
The use of local wisdom as learning sources and the empowerment of students’ Higher-Order Thinking Skills (HOTS) are the two components that must be carried out in the 21st-century biology learning. The purpose of this study was to explore the information about the application of local wisdom-based learning and HOTS-based assessment in Banjarmasin. This survey research involved 41 high school biology teachers in Banjarmasin who joined in Biology Teacher Working Group activities as research samples. The research instruments were questionnaires that were validated by experts. The data were analyzed using descriptive statistics in term of percentage. The findings showed that the teacher gave a positive response to the content of local wisdom to be a source of biology learning. In addition, they believed that through the learning, the students caring attitudes towards the potential and local wisdom of South Kalimantan were developed. Nonetheless, the empowerment of HOTS was not optimal as it was less frequent for the teachers to design HOTS-based learning in their class.